Dynamic contrast-enhanced MR imaging evaluation of perfusional changes and ablation zone size after combination embolization and ablation therapy - Chiang, Jason; Sparks, Hiro; Rink, Johann; Meloni, M. Franca; Hao, Frank; Sung, Kyung H.; Lee, Edward W. (Journal of vascular and interventional radiology, 2023)
Purpose - The objectives of this study were to assess the utility of dynamic contrast-enhanced magnetic resonance (MR) imaging in quantifying parenchymal perfusional changes after embolization and to characterize the association between pharmacokinetic (PK) parameters and final microwave ablation volume. - Materials and Methods - PK parameters from dynamic contrast-enhanced MR imaging were used to quantify perfusional changes in the liver after transarterial embolization of the right or left lobe in a swine liver model (n = 5). Each animal subject subsequently underwent microwave ablation (60 W for 5 minutes) of the embolized and nonembolized liver lobes. Changes in PK parameters from dynamic contrast-enhanced MR imaging were correlated with their respective final microwave ablation volumes in each liver lobe. - Results - Microwave ablation volumes of embolized liver lobes were significantly larger than those of nonembolized liver lobes (28.0 mL ± 6.2 vs 15.1 mL ± 5.2, P < .001). PK perfusion parameters were significantly lower in embolized liver lobes than in nonembolized liver lobes (Ktrans = 0.69 min−1 ± 0.15 vs 1.52 min−1 ± 0.37, P < .001; kep = 0.69 min−1 ± 0.19 vs 1.54 min−1 ± 0.42, P < .001). There was a moderate but significant correlation between normalized kep and ablation volume, with each unit increase in normalized kep corresponding to a 9.8-mL decrease in ablation volume (P = .035). - Conclusions - PK-derived parameters from dynamic contrast-enhanced MR imaging can be used to quantify perfusional changes after transarterial embolization and are directly inversely correlated with final ablation volume.